Institutions governance is critical to economic success: Evidence from Tanzania’s economic growth (Asian Journal of Economics and Business Management, 2023)
Economic performance is considered the fundamental cause of economic growth. Economic performance affects economic growth through the allocation of resources like physical and human capital. Unfortunately, there are few empirical studies showing institutions’ impact on Economic growth in Tanzania. This study aimed to examine the causal relationship between institutions and economic growth by focusing on the evidence from Tanzania Economic growth. More specifically, the study established the state or characteristics of key components of governance in economic production function of Tanzania. This is a time series study using econometric estimation to give empirical contents of the relationship between governance institutions and economic growth. Estimation techniques deployed to analyze the data were Regression approach within Ordinary Least Square (OLS), generalized Auto Regressive Distributed Lag (ARDL) and Error Correction Model (ECM) process.  The results revealed that a causal relationship of institutions has a positive and significant impact on economic growth in Tanzania. The study recommends that components of governance since are critical to economic growth should be emphasized to the public institutions for raising better performance in the country.  Therefore, the study concludes that institutional quality may lead to a sustainable increase in country’s income in the long run, and at the same time, success of any policy could be influenced by the soundness of institutions.